PENGARUH PEMAHAMAN PERATURAN PERPAJAKAN, KEWAJIBAN MORAL DAN TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Januanisa, Vina; Budiyarti, Nelly (Jurnal Nusa Akuntansi, 2024)
This study aims to analyze the influence of understanding tax regulations, moral obligations and tax amnesty on individual taxpayer compliance. This study was conducted on individual taxpayers registered at KPP Pratama Pondok Aren with a population of 427,078 taxpayers where the sample obtained by the slovin test was 100 individual taxpayers with a sampling technique using accidental sampling. The data used in this study are primary data collected using a questionnaire. The analysis technique uses multiple linear regression with the help of SPSS software version 22. The results of the analysis show that understanding tax regulations, moral obligations, and tax amnesty simultaneously have a positive effect on individual taxpayer compliance. Understanding tax regulations partially has a positive effect on individual taxpayer compliance. Moral obligations partially have a positive effect on individual taxpayer compliance. Tax amnesty partially has a positive effect on individual taxpayer compliance